Actualization of Fitrah in Islamic Education: (A Textual and Contextual Study of QS. Al-Rūm: 30 and the Hadith on Fitrah) - Faham Syah; Ihsanul Hakim (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
ENGLISH: Actualization of Fitrah in Islamic Education: (A Textual and Contextual Study of QS. Al-Rūm: 30 and the Hadith on Fitrah)Objective: This study aims to examine the actualization of the concept of fitrah in Islamic education through the analysis of QS. Al-Rūm verse 30 and related hadiths, and to formulate an integrative fitrah-based educational framework unifying exegesis, hadith, maqāṣid al-sharī‘ah, developmental psychology, and neuroscience. Methods: A qualitative approach was employed using a library research design, utilizing content analysis and thematic interpretation of primary sources and relevant scientific literature. Results: Fitrah is identified as an innate theological and humanistic potential oriented toward monotheism, morality, and holistic self-development. This multidisciplinary integration strengthens the theoretical foundations of curricula and pedagogical strategies, making them adaptive to learners' psychological and cognitive developmental stages. Conclusion: The fitrah-based Islamic education model offers a holistic paradigm for addressing moral degradation, spiritual crises, and digital culture disruptions. Contribution: This study enriches the theoretical discourse by repositioning fitrah as an integrative foundation for 21st-century Islamic education.INDONESIAN: Aktualisasi Fitrah Dalam Pendidikan Islam: (Studi Tekstual dan Kontekstual QS. Al-Rūm: 30 dan Hadis tentang Fitrah)Tujuan: Penelitian ini bertujuan mengkaji aktualisasi konsep fitrah dalam pendidikan Islam melalui analisis QS. Al-Rūm ayat 30 dan hadis terkait, serta merumuskan kerangka konseptual pendidikan berbasis fitrah yang mengintegrasikan tafsir, hadis, maqāṣid al-syarī‘ah, psikologi perkembangan, dan neurosains. Metode: Pendekatan kualitatif digunakan dengan desain studi kepustakaan melalui metode analisis isi dan interpretasi tematik terhadap berbagai sumber primer serta literatur ilmiah relevan. Hasil: Fitrah diidentifikasi sebagai potensi bawaan teologis dan humanis yang berorientasi pada tauhid, moralitas, serta pengembangan diri secara holistik. Integrasi lintas disiplin ilmu tersebut memperkuat landasan teoretis kurikulum dan strategi pedagogi yang adaptif terhadap fase perkembangan psikologis serta kognitif peserta didik. Kesimpulan: Model pendidikan Islam berbasis fitrah menawarkan paradigma alternatif yang solutif dalam menghadapi tantangan degradasi moral, spiritual, dan disrupsi budaya digital. Kontribusi: Studi ini memperkaya khazanah teoretis dengan memosisikan kembali konsep fitrah sebagai fondasi integratif pendidikan Islam abad ke-21 melalui sinergi otoritas teks klasik dan sains modern.